1997
DOI: 10.1016/s0014-5793(96)01392-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of cGMP and protein kinase G in nitric oxide‐induced apoptosis in the pancreatic B‐cell line, HIT‐T15

Abstract: Intracellular production of nitric oxide (NO) is thought to mediate the pancreatic B-cell-directed cytotoxicity of cytokines in insulin-dependent diabetes mellitus, and recent evidence has indicated that this may involve induction of apoptosis. A primary effect of NO is to activate soluble guanylyl cyclase leading to increased cGMP levels and this effect has been demonstrated in pancreatic B-cells, although no intracellular function has been defined for islet cGMP. Here we demonstrate that the NO donor, GSNO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 30 publications
6
76
0
Order By: Relevance
“…These results are in line with the suggestion that PKG may be involved in NO-induced apoptosis in insulin-secreting HIT T15 cells based on the data showing that the NO donor S-nitrosoglutathione and the permeable analog of cGMP stimulated apoptosis, an effect that could be inhibited by KT5823 (34). Mechanisms involving PKG in ␤-cells are poorly understood; our data show that they do not involve activation of Ca 2+ channels.…”
Section: Discussionsupporting
confidence: 91%
“…These results are in line with the suggestion that PKG may be involved in NO-induced apoptosis in insulin-secreting HIT T15 cells based on the data showing that the NO donor S-nitrosoglutathione and the permeable analog of cGMP stimulated apoptosis, an effect that could be inhibited by KT5823 (34). Mechanisms involving PKG in ␤-cells are poorly understood; our data show that they do not involve activation of Ca 2+ channels.…”
Section: Discussionsupporting
confidence: 91%
“…An increase in intracellular cAMP is of interest too, because a rise in cAMP may form part of the effector system controlling apoptosis in pancreatic -cells (Loweth et al 1997). It is therefore noteworthy that cell loss due to apoptosis is the first step we observed in the process of islet-to-cyst transformation.…”
Section: Discussionmentioning
confidence: 85%
“…cAMP-mediated information flow, however, appears to play an important role (Osaka & Sabban 1997, Ghee et al 1998, Yarwood et al 1998. This is of particular interest, because a rise in cAMP has recently been reported to form part of the effector system controlling apoptosis in pancreatic -cells (Loweth et al 1997), and cell loss is the first stage observed in the transformation of islets to duct epithelial structures (Yuan et al 1996). Moreover, during this transition, islets are maintained in medium supplemented with cholera toxin (CT), which is known to elevate intracellular cAMP.…”
Section: Introductionmentioning
confidence: 99%
“…8-bromoguanosine-cyclic GMP was found to augment glucose-induced Ca 2+ oscillations in mouse islets and to inhibit K ATP channel activity in mouse-intact beta cells [51]. Cyclic GMP was reported to mediate nitric oxide-induced apoptosis in the insulin-secreting cell line HIT-T15 [52].…”
Section: Cyclic Gmpmentioning
confidence: 99%